Pengaruh Layanan Penguasaan Konten Untuk Meningkatkan Keterampilan Regulasi Diri Dalam Belajar Pada Siswa Kelas VIII SMP Negeri 3 Kota Bengkulu - Shalindra Varadeba Hasanah; Syahriman; Rita Sinthia (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
The purpose of this study was to determine the effect of content mastery services to improve self-regulated learning skills in class VIII students of Junior High School Number 3 Bengkulu City. This research used quantitative experimental research with a one group pretest posttest design. The population in this study was 141 students, the sampling technique used intact group random sampling with a total of 25 students. Data was collected using a questionnaire and analyzed using t-test and the results of this research show a significant influence of content mastery services on improving self-regulated learning. The average self-regulated learning before being given content mastery service treatment was in the medium category and after being given content mastery service treatment was in the high category. Based on the research results, it is recommended that guidance and counseling teachers be able to use content mastery services to improve self-regulated learning skills. Keywords: Self-Regulated Learning Skills, Content Mastery